Forum Młodych Chirurgów The activity of protein C among neonates undergoing surgery for congenital heart defects with cardiopulmonary bypass - Szpecht, Dawid; Wojtalik, Michał; Mrówczyński, Wojciech; Poprawski, Grzegorz; Kempka-Dobra, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Introduction: Protein C can influence the postoperative outcome in neonates undergoing correction of congenital heart disease. Aim: The aim of this study was to: 1. analyze the activity of protein C among neonates undergoing CPB, 2. analyze the influence of pre- and perioperative infection risk factors on C protein activity changes, and 3. investigate C protein activities in children with and without postoperative infection. Material and methods: Eight infants were operated on using CPB in deep and moderate hypothermia (age 97.6 ± 83.8 days). Blood samples were drawn at 6 time points: before general anaesthesia, 5 minutes after the beginning of CPB, 5 minutes before disconnecting from CPB, 15 minutes after administering protamine, and on the second and third postoperative day. The activity of C protein was measured with a CoagChrom 3003 Coagulometr. Results: The mean baseline C protein activity was below the norm, decreased immediately after the institution of CPB and gradually increased to reach starting values at the end of observation. The changes were significant (p<0.0001). There were no significant statistical differences among children with and without infection risk factors. Similarly, present infection did not influence C protein activity. Conclusions: CPB exacerbates the preoperative deficit of C protein. The subsequent recovery is visible, but C protein activities do not reach normal ranges for the age group.